Development of Socio-Scientific Issues Based Reproduction E-Module to Enhance Critical Thinking Skills - Amalia, Fitri; Manalu, Kartika (Universitas Wiralodra, 2025)
This research focuses on the development of an e-module integrating the Socio-Scientific Issues (SSI) approach in teaching human reproductive system material to enhance critical thinking skills among 11th-grade students at SMAS Cerdas Murni. The study was motivated by the low level of students' critical thinking skills, the predominance of conventional teacher-centered methods, and the lack of interactive and contextual learning materials that can connect concepts to real-life issues. The research employed a Research and Development (R&D) design with the 4D model (Define, Design, Develop, and Disseminate). The scope was limited to the development stage due to time and budget constraints. The developed SSI-based e-module was validated by subject matter experts, yielding a feasibility score of 96.43%, and by media experts, yielding a score of 95.31%, both categorized as “highly feasible.” Practicality testing by biology teachers and students resulted in percentages of 96.67% and 95.33%, respectively, indicating the e-module is “very practical” for classroom use. Effectiveness was measured through an N-Gain analysis, producing a score of 0.80, which falls into the “high” category and demonstrates a significant improvement in students’ critical thinking skills. These findings indicate that the SSI-based e-module is feasible, practical, and effective in supporting the development of critical thinking skills, providing an innovative and engaging alternative to conventional biology teaching on the human reproductive system. The module has potential for broader implementation in senior high school biology learning.